2017
DOI: 10.1101/217828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden variation in polyploid wheat drives local adaptation

Abstract: Abstract:Wheat has been domesticated into a large number of agricultural environments and has a remarkable ability to adapt to diverse environments. To understand this process, we survey genotype, repeat content and DNA methylation across a bread wheat landrace collection representing global genetic

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The addition of novel data types such as epigenetics and chromatin conformation may contribute to improved wheat phenotypic prediction. Initial studies reveal epigenetic differences amongst landraces (Gardiner et al ., 2018b), which are likely to also be observed in elite material. Incorporating diverse data types (genomics, epigenomics and environmental data) may enable more accurate predictions of phenotypes.…”
Section: Looking Forwardmentioning
confidence: 93%
See 2 more Smart Citations
“…The addition of novel data types such as epigenetics and chromatin conformation may contribute to improved wheat phenotypic prediction. Initial studies reveal epigenetic differences amongst landraces (Gardiner et al ., 2018b), which are likely to also be observed in elite material. Incorporating diverse data types (genomics, epigenomics and environmental data) may enable more accurate predictions of phenotypes.…”
Section: Looking Forwardmentioning
confidence: 93%
“…This collection has been purified by single‐seed descent from which many genomic and genetic resources have been developed. Genotyping of this collection revealed extensive novel genetic (Winfield et al ., ) and epigenetic (Gardiner et al ., 2018b) diversity, which was absent from modern cultivars. A core set of 107 accessions was used to generate nested association mapping populations (Wingen et al ., ), all of which were genotyped, have genetic maps available, and are free to access (http://wisplandracepillar.jic.ac.uk/).…”
Section: Use Of Natural Variation For Trait Discoverymentioning
confidence: 94%
See 1 more Smart Citation
“…In the last decades, exotic parents have been used in breeding programmes with the aim of introducing greater diversity into elite gene pools (Singh et al ., ). The exotic parents that are most frequently used are those from the primary gene pool represented by germplasm that share a common genome but that have become isolated from mainstream gene pools such as landraces (Reynolds et al ., ,b), which have been shown to be not only genetically, but epigenetically diverse (Gardiner et al ., ). The secondary gene pool that has also been used is represented by closely related genomes that can be utilised through inter‐specific hybridisation, and would include the development of so‐called ‘synthetic’ or ‘re‐synthesised’ wheat, where a tetraploid durum wheat has been hybridised with Aegilops tauschii , the ancestral donor of the D genome, to recreate hexaploid bread wheat (Mujeeb‐Kazi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, an array of investigations in diverse plants have documented that allopolyploidization induces a cascade of rapid epigenetic modifications such as altered DNA methylation via differential titration of non-coding RNAs [17][18][19][20][21]. Analyses of homoeologous DNA methylation pattern in hexaploid wheat suggested that tri-genome methylation is significantly more conserved across the accessions compared to uni-and bigenome methylation [22,23]. Beside DNA methylation, histone modifications also play important roles in polyploid formation and stabilization [21,24].…”
Section: Introductionmentioning
confidence: 99%